KOMI-PERMYAK MEAT - A DOUGH DISH OF THE FORMING OF THE ALL-RUSSIAN MARKET ERA OR THE ANTHROPOLOGY OF PELMEN - Korchagin, P.A. (Perm Federal Research Centre Journal, 2016)
Pelmeni as a special culinary product appeared in the first half of the XVII century on the territory of modern Kochevskoy and Kosinskiy districts of Komi-Permyak Okrug of Perm Krai. On the "Moscow path" section Kai - Ukseevskoe - Kosa - Solikamsk this dish was very popular with coachmen of the great many sledges transporting grain supplies from Pomor’e districts to Siberia. It is in Komi Okrug where the earliest sources of the onomastic kind were recorded. For example, last names of Pelmennikovs’ and Pelmenevs’, the owners of which made the production and sale of pelmeni their trade.